Blended Learning with the Teaching Personal and Social Responsibility Approach in Learning Physical Education Sports and Health and Character in the New Normal Era - Raharjo, Hermawan Pamot; Setyawati, Heny (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2023)
This study aims to develop a learning model with the TPSR approach. The learning materials studied are Physical Education, Sports and Health (PESH) and character physical education, basic locomotor movement patterns for the lower grades of elementary school. This research method uses research and development, consist of five main stages: 1) Needs Analysis, 2) Planning and Design, 3) Expert validation, 4) Field trials, and 5) Product revision. The subjects of this study were all elementary school students in Gunungpati, Semarang. Data analysis using the analytical description. Research results: 1. Need to improvise the learning process of locomotor basic motion material. 2. There are problems in implementation in the field. 3. Teachers teach only based on their experience. The results of the Small andLarge Scale Trials showed an increase in students' attitudes, knowledge values, and locomotor movement abilities. The results of the Feasibility Test also showed an increase in the attitude value, knowledge value, and locomotor movement ability of students.